Insect Frass: A Promising Fertilizer for Sustainable Agriculture - Kumar, M. Anil; Rajashekhar, Mandla; Vaishnavi, A.; Sahithi, K.; Bharghavi, K.; Praveen, S. Leela; Asritha, Ch. (Chronicle of Bioresource Management, 2024)
With the increasing global human population rapidly, there is demand for alternative animal protein sources. Mass breeding of insects for feed and food has emerged as a notable alternative. Byproduct of this process is insect frass (excreta), produced up to 40 times more than the actual insect biomass. Utilizing frass as an organic fertilizer, a viable alternative to chemical fertilizers in sustainable agriculture. The article highlights the merits of insect frass in sustainable agriculture. (1) Frass serves as source of nutrients for the soil, particularly nitrogen, offering easily absorbable elements for plants. (2) The composition of frass includes biomolecules and microorganisms that actively promote plant growth, enhances plants resilience to environmental stresses, bolstering their resistance to diseases and pests.